THE ANALYZING OF AMBIGUITY ON STUDENTS’ WRITING MADE BY STUDENTS IN SMK DHARMA BAKTI MEDAN - Baren, Elya Batu; Ginting, Fiber Yun A.; Tarigan, Karisma E. (Kairos English Language Teaching Journal, 2021)
The aims of this study were to figure out the casual factors of ambiguity found in students writing. The subject of this study was the students of Class XI-TKR of SMK Dharma Bakti Medan. The research design was in the form of descriptive qualitative research. The instrument of collecting data was the students’ sheet of English writing text. In conclusion, the most dominant ambiguity in lexical meaning found in writing text by Class XI-TKR of SMK Dharma Bakti Medan was polysemy ambiguity. There were 10 casual factors of why ambiguity found in students’ writing text based on the analysis of the structure of sentence in students’ English writing. The most reasons were: (1) the students did not give the specific details in their writing, usually they preferred the short writing, (2) there were several vocabularies which could be reasonably interpreted more than one way or reasonably interpreted more than one thing, (3) the students felt confused to find appropriate vocabularies to express the meaning. As a result, they sometimes left the sentence undone or hanged without a clear idea, due to the lack of vocabularies. The analysis of ambiguity in lexical meaning that made by students of Class XI-TKR of SMK Dharma Bakti Medan revealed that students should learn semantic as the main subject in English writing to understand multiplicity of meanings.